Forensic Monitoring Project Report: Bukova Greda Exhumation Republika Srpska Commission on Missing and Tracing - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Connor, Melissa The Republika Srpska Commission on Missing and Tracing recovered two sets of skeletal remains on 21 August at a cemetery in Bukova Greda. Place of Exhumation: Bukova Greda Date of Exhumation: 21 August 1998 Minimum Number of Exhumed Individuals: 002